Hong Kong's young children : their early development and learning - Opper, Sylvia P. (Hong Kong University Press, 1996)
The formative years from three to six are a crucial period in human development. However, although a great deal of information is available on the development of Western children during this period, little research has been done on their counterparts in Hong Kong. This publication, which is the result of a large-scale developmental study of three- to five-year-olds in Hong Kong, presents detailed information on five areas of development and learning: physical, social-emotional, cognitive, language, and preacademic. Data collection was carried out at three points during the academic year. The resulting information covers overall development for the three ages, as well as specific details for each age level at the beginning, middle and end of the academic year. Such details provide a crucial data base that can be used by parents and by professionals involved in the care and education of preschool children, and on which future research can build.